Effect of a Handover Tool on Efficiency of Care and Mortality for Interhospital Transfers. Issue 1 (1st January 2017) - Theobald, Cecelia N.; Choma, Neesha N.; Ehrenfeld, Jesse M.; Russ, Stephan; Kripalani, Sunil
Abstract : BACKGROUND: Interhospital transfer is frequent, and transferred patients experience delays in the provision of care and higher mortality rates when compared to patients directly admitted. The interhospital handover is a key opportunity to improve care but has not been evaluated. OBJECTIVE: To determine the effect of a universal handover tool on timeliness of care, length of stay (LOS), and mortality among interhospital transfer patients. DESIGN, SETTING, AND PATIENTS: Retrospective cohort of patients transferred to an academic medical center between July 1, 2009 and December 31, 2010 with interrupted time‐series design. INTERVENTION: One‐page handover tool containing information critical for immediate patient care instituted hospital‐wide on July 1, 2010. The handover tool was completed by the transferring physician and available for review before patient arrival. MEASUREMENTS: Time‐to‐admission order entry, LOS after transfer, in‐hospital mortality RESULTS: There was no significant change in the time‐to‐admission order entry after implementation (47 minutes vs. 45 minutes, adjusted P = 0.94). There was a nonstatistically significant reduction in LOS after implementation (6.5 days vs. 5.8 days, adjusted P = 0.06). In‐hospital mortality for transfer patients declined significantly in the postintervention period from 12.0% to 8.9% (adjusted odds ratio, 0.68; 95% confidence interval, 0.47 – 0.99, P = 0.04). There was no change in mortality for the concurrent control group. CONCLUSION: Implementation of a standardized handover tool for interhospital transfer was feasible and may be associated with significant reductions in length of stay and mortality. Widespread adoption of similar tools may improve outcomes in this high‐risk population.